EFEKTIVITAS BUKU SAKU EDUKATIF DALAM MENINGKATKAN KEMAMPUAN BACA TULIS HURUF HIJAIYAH ANAK USIA DINI DI PERUM GPA DESA NGIJO KEC. KARANGPLOSO - Hamidi, Amrozi; Wijokongko, Danar; Romelah, Romelah (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2025)
Purpose of the study: The purpose of this activity is to improve the ability of early childhood in recidential complex GPA Desa Ngijo Kec. Karangploso to read and write Hijaiyah letters. Methodology: The implementation method is a type of field action oriented towards community empowerment. Main Findings: The teaching of reading and writing Hijaiyah letters to early childhood in recidential complex GPA Desa Ngijo, Karangploso Subdistrict, is still done conventionally without the use of innovative learning media. Applications of this study: This community service is useful for the community in recidential complex GPA, Ngijo Village, Karangploso Subdistrict, to determine the effectiveness of using educational pocket books in teaching Hijaiyah letters to early childhood. Novelty/Originality of this study: The community in recidential complex GPA, Ngijo Village, Karangploso Subdistrict, can use simple and portable educational pocket books as a medium to improve the ability of early childhood to read and write Hijaiyah letters